Chalcogen alloying for band structure modulation of antimony chalcogen iodide alloy: 1D van der Waals materials SbSI-SbSeI system - Jeon, Jiho; Kang, Jinsu; Zhang, Xiaojie; Choi, Kyung Hwan; Jeong, Byung Joo; Woo, Chaeheon; Dong, Xue; Kim, Sang Hyuk; Park, Jae Hyuk; Baik, Jeong Min; Oh, Hyung Suk; Yu, Hak Ki; et al. (CrystEngComm, 2023)
SbSI and SbSeI materials, which are one-dimensional materials based on van der Waals bonds, have the same crystal structure and physical property changes because of their differences in lattice constants. Therefore, controlling the band structure of these materials in accordance with the mixing ratio of S and Se is important. In this study, SbSI, SbSeI, and alloys with intermediate compositions were synthesized, and their crystal and band structures were analyzed. Results showed a lattice strain proportional to the composition of the S-Se mixture, which was synthesized as a stable phase without phase separation. As S was substituted with Se, the band gap decreased. These results could be utilized in various fields of optoelectronic devices where Sb (S or Se) I series is primarily applied.
Keywords: Band structure modulation; Chalcogens; Crystals structures; Material-based; One-dimensional materials; Property changes; Structure and physical properties; Synthesised; Van der Waal; Van der Waal bonds